Mystery and secrecy in the Nag Hammadi collection and other ancient literature : ideas and practices : studies for Einar Thomassen at sixty - Thomassen, Einar.; Bull, Christian H.; Lied, Liv Ingeborg.; Turner, John Douglas. (Nag Hammadi and Manichaean Studies, 2012)
Mystery and secrecy were central concepts in the ritual, rhetoric, and sociological stratification of antique Mediterranean religions. That the ultimate nature and workings of the divine were secret, and either could not or should not be revealed except as a mystery for the initiated, was widely accepted among Pagans, Jews, and then Christians, both Gnostic and otherwise. The similarities and differences in the language of mystery and secrecy across religious and cultural borders are thus crucial for understanding this important period of the history of religions. The present anthology aims to present and analyze a wide selection of sources elucidating this theme, reflecting the correspondingly wide scholarly interests of Professor Einar Thomassen in honor of his 60th birthday.